DETERMINANTS OF ENTREPRENEURIAL CAREER CHOICE: AN EMPIRICAL STUDY OF ACCOUNTING STUDENTS - Septiana, Laela Ma’rifatika; Kholid, Muamar Nur (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2022)
The purpose of this study was to ascertain the factors that influence accounting students' intentions to become entrepreneurs. The Theory of Planned Behavior (TPB) served as the theoretical foundation for this investigation. Subjective norms were divided into two viewpoints in this study: injunctive norm and descriptive norm. Purposive sampling was used to select respondents for this study. The sample criteria for this study were accounting students who enrolled in an undergraduate program at universities in Yogyakarta. According to the data gathered, 213 respondents completed this research questionnaire. The data were analyzed using the PLS-SEM approach in conjunction with the SmartPLS 3.0 software. The findings of this study revealed that entrepreneurial intention was positively influenced by attitude and perceived behavioral control. Meanwhile, self-confidence and creativity had a positive effect on attitude. Additionally, the study's findings indicated that business environment and training had a positive effect on perceived behavioral control. Both the injunctive and descriptive norm variables showed a favorable effect on intention, but the effect was not statistically significant. This study revealed the factors that influence accounting students' intentions to become entrepreneurs, which might assist lecturers and program directors to encourage accounting students to pursue entrepreneurial endeavors.JEL: M10, M40, L26